Relaksasi Benson Terhadap Tingkat Persepsi Nyeri pada Pasien Post Laparatomy di RSUD Nyi Ageng Serang. - Agus Renaldi; Maryana Maryana; Jenita Doli Tine Donsu (Caring : Jurnal Keperawatan, 2020)
Background: In studies suggest that post-laparotomy pain occurs in 15% of cases, potentially 35% of pain. Pain is a major problem in the treatment of post operative pain which is a defense mechanism that arises when there is damage to tissue and cause the individual to react in a way memundahkan painful stimulus. Aim: Identifying benson relaxation effect on the rank of the perception of pain in post-laparotomy patients in hospitals Nyi Ageng Serang. Method: This type of research is a quasi-experimental study. This study design using pre-test and post-test design with control group. In the intervention group was given treatment in the form of benson relaxation, while the control group was not given relaxation benson that her pain will be measured by the Numeric Rating Scale (NRS). The samples in this research were 35 respondents 35 respondents intervention group and the control group. The sampling technique used is consecutive sampling. Data collection from January to March 2020. Results: The data collected were processed using the Wilcoxon test and Mann Whitney test. Wilcoxon test results in the intervention group was obtained p = 0.000 (p <0.05) and the control group was obtained p = 0.000 (p <0.05). At the Mann Whitney test was obtained p = 0.000 (p <0.05), so that Ha is accepted. Conclusion: There is the influence of Benson relaxation therapy on the level of pain perception in patients with post-laparotomy.